PENGARUH JUMLAH BIBIT PER LUBANG TANAM DAN DOSIS PUPUK N, P DAN K TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH (Oryza sativa L.) DENGAN METODE SRI - Joko Susilo; Ardian '; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The rice plant (Oryza sativa L.) is a kind of plant that produce rice which is the become main food for majority of Indonesian people. The total of people that rise increasingly must balance with the increasing of  rice production. One of the methods to get the increasing of rice production is applying the System of Rice Intensification (SRI).This research aims to determine the intraction of seeds number and the best fertilizer on the growth and production of lowland rice. The experiment sites in lowland field of Balai Benih Induk Holtikultura, Kaharudin Nasution Street, Padang Marpoyan, Pekanbaru City, Riau Province.Started on March Until July 2012. Research using Randomized Block Design (RBD) factorial, the first factor consists of 4 threatments (1 seed/hole,2 seeds/hole, 3 seeds/hole, 4 seeds/hole) and the second factor consists of  3 treatments: Fertilizer Urea, SP-36, KCl,  P1( 60, 30, 30) g,  P2 (90, 60, 60) g and P3 (120, 90, 90) g. The measured parameters were plant height, number of totaltillers, number of productive tillers, harvest, long tassel, tassel amount per branch, 1000 seed grain weight,  weight of dry unhusked rice per plot. Data was analyzed by analysis of variance and further test by Duncan’s Multiple Range Test (DNMRT) at the level of 5%. The best treatment was obtained at 3 seeds per planting hole and Urea fertilizer dosage of 120 g/plot + SP-36 60 g/plot + KCl 60 g/plot to increase the production of milled rice per plot. Keywords: Number of Seeds, Fertilizers, Rice, SRI